Regulation of Immune Responses by mTOR - Powell, Jonathan D. (2011)
mTOR is an evolutionarily conserved serine/threonine kinase that plays a central role in integrating environmental cues in the form of growth factors, amino acids, and energy. In the study of the immune system, mTOR is emerging as a critical regulator of immune function because of its role in sensing and integrating cues from the immune microenvironment. With the greater appreciation of cellular metabolism as an important regulator of immune cell function, mTOR is proving to be a vital link between immune function and metabolism. In this review, we discuss the ability of mTOR to direct the adaptive immune response. Specifically, we focus on the role of mTOR in promoting differentiation, activation, and function in T cells, B cells, and antigen-presenting cells.